Distal renal tubular acidosis and lethargy associated with zonisamide treatment in a dog with idiopathic epilepsy. Issue 6 (2nd August 2022) - Itoi, Takamasa; Akashi, Natsuki; Shimizu, Yuki; Sugimoto, Keisuke; Hata, Akihisa; Kutara, Kenji; Miyama, Takako Shimokawa; Kanda, Teppei
Abstract: A 3‐year‐old neutered male golden retriever administered zonisamide for the treatment of seizures showed lethargy and had normal anion gap metabolic acidosis with hypokalaemia, hyperchloremia, and alkaline urine. The serum zonisamide concentration was close to the upper limit, which raised a suspicion of adverse effects of zonisamide. This is the first report showing that the fractional excretion of bicarbonate after compensation for the plasma bicarbonate concentration by a sodium bicarbonate infusion was approximately 5%, indicating distal renal tubular acidosis (RTA). The serum zonisamide concentration decreased, and adverse effects were abated by reducing the zonisamide dosage. Diagnostic therapy with bicarbonate served as a means of compensating for bicarbonate deficiency and contributed to the clinical diagnosis of the condition in zonisamide‐associated RTA in dogs. Abstract : Zonisamide is a second‐generation antiepileptic drug that has been widely used in recent small animal practice, for treatment of seizures associated with epilepsy. Although its frequency may be fairly rare, zonisamide can cause an adverse effect of distal renal tubular acidosis (RTA) as reported in a human patient. Here, we report a clinical case and laboratory findings of distal RTA associated with zonisamide in a dog.